2009
DOI: 10.1002/ejoc.200800795
|View full text |Cite
|
Sign up to set email alerts
|

New Terpenoid Constituents of the Southwestern Caribbean Sea Whip Pseudopterogorgia elisabethae (Bayer), Including a Unique Pentanorditerpene

Abstract: Seven structurally diverse terpenoids, including four diterpenes, a norditerpene, a bisnorditerpene, and a biogenetically related pentanorditerpene, have been isolated from the hexane extract of the Caribbean gorgonian octocoral Pseudopterogorgia elisabethae, collected near the island of San Andrés, Colombia. The structures of all the new compounds were determined by detailed spectroscopic analysis and chemical derivatization. Many of the purified isolates were evaluated in vitro as potential agents to treat n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 27 publications
(27 reference statements)
0
28
0
Order By: Relevance
“…84 Isoelisabethatriene (58) was originally obtained as a semisynthetic product upon treatment of 57 with SeO 2 in the presence of trimethylsilyl polyphosphate (PPSE), 84 but was later identified from an extract of P. elisabethae collected in the Florida Keys. 96,98 Follow-up biological screening of elisabethin D, whose structure was also confirmed by X-ray diffraction analysis, indicated no significant in vitro cancer cell cytotoxicity in the NCI's three-cell-line tumor panel, nor was it active in the NCI's test for agents active against the HIV. A chemical investigation of this gorgonian coral from San Andrés Island led to the isolation of the closely related bicyclic diterpene, elisabethatrienol (59).…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…84 Isoelisabethatriene (58) was originally obtained as a semisynthetic product upon treatment of 57 with SeO 2 in the presence of trimethylsilyl polyphosphate (PPSE), 84 but was later identified from an extract of P. elisabethae collected in the Florida Keys. 96,98 Follow-up biological screening of elisabethin D, whose structure was also confirmed by X-ray diffraction analysis, indicated no significant in vitro cancer cell cytotoxicity in the NCI's three-cell-line tumor panel, nor was it active in the NCI's test for agents active against the HIV. A chemical investigation of this gorgonian coral from San Andrés Island led to the isolation of the closely related bicyclic diterpene, elisabethatrienol (59).…”
Section: Introductionmentioning
confidence: 93%
“…Biological screening studies indicated that benzoxazoles 55 and 56 are strong growth inhibitors of M. tuberculosis H 37 Rv. 96 2.11.2.1.2(iii) Elisabethanes and related metabolites (compounds reported ¼ 11) In 1998, a routine inspection of the 1 H-and 13 C-NMR data of the hexane solubles of P. elisabethae collected near San Andrés Island revealed that the majority of the compounds present in that specimen possessed distinctively different carbon frameworks quite unlike those previously described for the aglycon portion of the Pss and seco-pseudopterosins. [80][81][82][83] 2.11.2.1.2(ii) Serrulatanes (compounds reported ¼ 16) Elisabethatriene (57), whose molecular structure was proposed based on spectroscopic data alone, was isolated and purified using a radioactivity-guided isolation protocol from a specimen of P. elisabethae collected in May 1999 at Sweetings Cay in the Bahamas.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations